Low Serum Level of High-density Lipoprotein Cholesterol Is Associated with Gastric Cancer Regardless of Sex and Tumor Stage - Su Youn Nam; Jihyeon Jeong; Won Kee Lee; Seong Woo Jeon (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims HDL cholesterol (HDL-C) may have anti-tumor effects; however, the effects remain unclear. Thus, this study aimed to investigate sex- and tumor stage-specific association of hyperglycemia and HDL-C with gastric cancer. Materials and Methods We used the National Health Insurance Service data. All participants underwent gastric cancer screening between January and December 2011. Hyperglycemia and HDL-C levels were categorized according to the World Health Organization guideline and Adult Treatment Panel III. Adjusted regression analysis was performed using ORs and 95% CIs. Results Gastric cancer was detected in 10,417 of 5.49 million individuals (2.43 million men). Hyperglycemia (OR, 1.28; 95% CI, 1.20~1.36) and low HDL-C levels (OR, 1.41; 95% CI, 1.35~1.48) were associated with gastric cancer. In the sub-analysis by sex, hyperglycemia (≥126 mg/dL) was associated with gastric cancer in both men (OR, 1.26; 95% CI, 1.18~1.36) and women (OR, 1.32; 95% CI, 1.17~1.49). Low HDL-C levels were associated with gastric cancer in both men (OR, 1.49; 95% CI, 1.40~1.58) and women (OR, 1.32; 95% CI, 1.27~1.42). In the sub-analysis by tumor stage, hyperglycemia was associated with both early (OR, 1.14; 95% CI, 1.08~1.20) and advanced gastric cancer (OR, 1.39; 95% CI, 1.26~1.55). Low HDL-C levels were also associated with early (OR, 1.34; 95% CI, 1.27~1.41) and advanced gastric cancer (OR, 1.92; 95% CI, 1.74~2.13). Conclusions Hyperglycemia and low HDL-C levels are consistently associated with gastric cancer regardless of sex or tumor stage.